SIGNS OF REPRODUCTIVE QUALITIES OF SOWS OF DIFFERENT OPERATING VALUE AND THE LEVEL OF THEIR DISCRETION - Khalak, V. I.; Il’chenko, M. O.; Petulko, P. V. (Scientific Progress & Innovations, 2020)
The indicators of reproductive qualities of sows of Large White breed taking into account their operational value are investigated, and the level of discreteness of the specified group of signs and economic efficiency of experimental results is calculated. The study was conducted on the breeding farm for breeding Large White pigs at “Druzhba-Kaznacheiivka” LLC, Dnipropetrovsk region and the laboratory of animal husbandry of the State Institution Institute of Grain Crops of the National Academy of Agrarian Sciences of Ukraine. The evaluation of sows of Large White breed on the main indicators of adaptation level and reproductive qualities in the group (S) and the population as a whole (σ) was carried out taking into account the following quantitative characteristics: life expectancy, months, duration of breeding use, amount of farrowing ((S1, σ1), total piglets, net (S2, σ2), live piglets, net (S3, σ3), fertility (S4, σ4), nest weight at the time of weaning at the age of 28 days, kg (S5, σ5), safety,%, duration of intergrowth period, days, number of unproductive days per farrowing. The operational value of the animals of the main herd was investigated by the method of Koriazhnov E. V. (1985), the level of discreteness (D) – Seromolota V. V., Sviatchenko S. I. (1984). Biometric processing of the obtained research results was performed according to the method of G. F. Lakin (1990). It was found that sows of Large White breed of controlled herd met the minimum requirements of class I and elite class as to the main indicators of reproductive qualities (multiplicity, goal; weight of the nest at the time of weaning at the age of 28 days, kg). A significant difference between the groups of high operational value and low operational value animal categories was established by the following indicators: life expectancy, month (29.9 months, td=13.71), the duration of breeding use, months (29.6 months, td=14.50), farrowings were obtained (5.7 farrowings, td=14.50), ‘total number of piglets was obtained, ch. (70.5 heads, td=13.85), obtained live piglets obtained, heads (67.7 heads, td=20.83), fertility, heads (3.3 heads, td=10.31), nest weight at the time of weaning at the age of 28 days (6.5 kg, td=2.55). The discreteness factor (D) of the reproductive qualities traits of sows of different operational value ranged from 0.765 to 0.992. The maximum increase in additional products on the indicator of nest weight at the time of weaning at the age of 28 days, kg was obtained from sows of the category of high operational value – 6.03 %.